A Study of Contact Tracing Applications for Containing the Spread of Covid-19- A Global Perspective (International Journal of Innovative Research in Computer Science & Technology, 2022)
In order to contain the spread of pandemic  Covid- 19, most of the countries across the globe have come  up with the contact tracing applications commonly known as  “Contact Tracing Apps”. Transparency, privacy and security  of user’s data are the major concerns that are associated with  the successfulness of a contact tracing app. The success of a  contact tracing app can be measured by looking at the  segment of the population using the app. The Government of  India launched Aarogya Setu as a mobile application to help  to contain the spread of Covid- 19 by providing mechanisms  to trace the contacts of an infected individual, so that the  individuals who have come into the contact of an infected  individual, can be isolated and quarantined as per the  protocol issued by the government from time to time and  thereafter can be medicated. Aarogya Setu Application  serves as a preventive measure that one can take to keep  himself/ herself informed, if the individuals whom he/ she  has been in contact is not a Covid- 19 patient. Aarogya Setu  is a technological endeavour undertaken by the Government  of India that encompasses the software technology and  internet technology. Majority of the countries across the  world have adopted the technology based solutions for the  purpose of contact tracing in the wake of Covid- 19.
Keywords: Contact Tracing App; ICT; Digital Divide; Privacy